ETHICS PSYCHOLOGICAL RESEARCH AND INTERVENTION IN WORK WITH CHILD ABUSE AND NEGLECT - L. V. Skitnevskaya (Вестник Мининского университета, 2017)
The article examines the key ethical issues that must be addressed in any study involving children and adolescents who are victims of violence and abuse. Psychological research and intervention is a social interaction and focus on achieving positive social goals, organization and holding of which requires compliance with professional ethical standards. Moral and ethical principles of specialists working with children and adolescents are part of the totality of universal norms, they include the most General rules of examination, preventive unnecessary or incompetent use of methods and techniques of diagnosis and intervention. Regardless of the condition of the subject, the researcher must always be sensitive to him, compassionate and interested in his fate. The article also highlights the issue of mandatory procedure for the announcement and signing of all research participants and/or intervention Informed consent, confidentiality and anonymity.